2023
DOI: 10.3389/fmicb.2023.1113540
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive molecules from haloarchaea: Scope and prospects for industrial and therapeutic applications

Abstract: Marine environments and salty inland ecosystems encompass various environmental conditions, such as extremes of temperature, salinity, pH, pressure, altitude, dry conditions, and nutrient scarcity. The extremely halophilic archaea (also called haloarchaea) are a group of microorganisms requiring high salt concentrations (2–6 M NaCl) for optimal growth. Haloarchaea have different metabolic adaptations to withstand these extreme conditions. Among the adaptations, several vesicles, granules, primary and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 154 publications
1
6
0
Order By: Relevance
“…A number of previous studies also showed that halophilic archaea includingHaloferax , Halobacterium, Halococcus , Haloarcula , and Halorubrum have heavy metal resistance genes on their plasmids and chromosomal DNA. These microorganisms help plants to grow under saline polluted soils [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies also showed that halophilic archaea includingHaloferax , Halobacterium, Halococcus , Haloarcula , and Halorubrum have heavy metal resistance genes on their plasmids and chromosomal DNA. These microorganisms help plants to grow under saline polluted soils [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Halophilic archaeal genera includingNatrinema, Halobacterium and Halococcus have been reported for P-solubilization and production of organic acids such as citric, succinic, oxalic, lactic, acetic and isovaleric acids [20,26]. Halophilic archaea isolated from hypersaline polluted environments also have the ability to tolerate heavy metal resistance for nickel, cadmium, uranium, chromium and zinc [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they produce other biomolecules with high biotechnological interest, like carotenoids (Flemming, 2016;Giani et al, 2019;Giani et al, 2022;Giani et al, 2021;Pfeifer et al, 2021) and exopolysaccharides (Flemming, 2016;Costa et al, 2018;Blackburn and Green, 2022). Besides, some haloarchaea can be used in the bioremediation processes to remove heavy metals and inorganic anions from brines and salty water (Oren, 2010;Nájera-Fernández et al, 2012;Martínez-Espinosa et al, 2015;Hou and Cui, 2018;Zuo et al, 2018;Pacholak et al, 2021;Pfeifer et al, 2021;Martínez et al, 2022;Moopantakath et al, 2023). Within haloarchaea, the most promising microorganism is Haloferax mediterranei (Pfeifer et al, 2021;Hagagy et al, 2022;Costa et al, 2023;Diankristanti et al, 2023), because it can synthesize PHBV without using any HV precursor (as required by other microorganisms) and can use different carbon sources to accomplish it (Tan et al, 2014b;Han et al, 2015;Parroquin-Gonzalez and Winterburn, 2023).…”
Section: Biological Synthesis Of Phasmentioning
confidence: 99%
“…Haloarchaea have attracted global scientific attention due to their unique features related to the molecular machinery of nitrogen, biodegradable polymers, and carotenoid metabolism; their easy manipulation; their reduced space requirements for cultivation compared to other organisms like microalgae or yeast from which highly marketed compounds can be obtained; and their capacity to produce a wide array of biomolecules and metabolites with potential biotechnological applications compared to plants, bacteria, fungi, or eukaryotic algae [8,9]. Their remarkable resilience and functionality even in the face of challenging environmental conditions, including high salinity, intense ultraviolet (UV) radiation, elevated ion concentrations, and extreme temperatures and pH, make them good model organisms to be used as cell factories for different purposes compared to their bacterial counterparts [10][11][12].…”
Section: Introductionmentioning
confidence: 99%